2020
DOI: 10.33321/cdi.2020.44.53
|View full text |Cite
|
Sign up to set email alerts
|

The first 2 months of COVID-19 contact tracing in the Northern Territory of Australia, March–April 2020

Abstract: The Northern Territory (NT) Centre for Disease Control (CDC) undertook contact tracing of all notified cases of coronavirus disease 2019 (COVID-19) within the Territory. There were 28 cases of COVID-19 notified in the NT between 1 March and 30 April 2020. In total 527 people were identified as close contacts over the same period; 493 were successfully contacted; 445 were located in the NT and were subsequently quarantined and monitored for disease symptoms daily for 14 days after contact with a confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 10 publications
1
54
0
Order By: Relevance
“…After a household member is confirmed to be infected with SARS-CoV-2, household or family contacts are identified, followed for a short duration of time (e.g., two weeks), and tested if eligible for testing according to national testing guidelines to ascertain secondary infections. Index cases were identified by passive surveillance, 21 , 28 , 29 , 31 , 38 – 40 , 43 , 44 , 49 51 active surveillance of key populations (e.g., travelers from areas with active SARS-CoV-2 transmission, and individuals detected by neighborhood fever screenings), 25 , 27 , 34 both active and passive surveillance, 14 , 15 , 17 – 20 , 22 , 24 , 26 , 30 , 32 , 33 , 35 , 36 , 41 , 46 , 48 , 52 , 53 or regional seroprevalence surveys. 42 , 45 We did not include case reports or cluster investigations that focused on individual households or families in an effort to reduce publication bias.…”
Section: Review Of Transmissibility Of Sars-cov-2 In Households and Fmentioning
confidence: 99%
See 4 more Smart Citations
“…After a household member is confirmed to be infected with SARS-CoV-2, household or family contacts are identified, followed for a short duration of time (e.g., two weeks), and tested if eligible for testing according to national testing guidelines to ascertain secondary infections. Index cases were identified by passive surveillance, 21 , 28 , 29 , 31 , 38 – 40 , 43 , 44 , 49 51 active surveillance of key populations (e.g., travelers from areas with active SARS-CoV-2 transmission, and individuals detected by neighborhood fever screenings), 25 , 27 , 34 both active and passive surveillance, 14 , 15 , 17 – 20 , 22 , 24 , 26 , 30 , 32 , 33 , 35 , 36 , 41 , 46 , 48 , 52 , 53 or regional seroprevalence surveys. 42 , 45 We did not include case reports or cluster investigations that focused on individual households or families in an effort to reduce publication bias.…”
Section: Review Of Transmissibility Of Sars-cov-2 In Households and Fmentioning
confidence: 99%
“…Many studies only included household contacts, 14 , 26 , 28 , 29 , 31 , 35 , 37 , 38 , 40 , 41 , 43 , 49 , 50 , 53 but others included family members, 15 , 20 , 21 , 23 , 27 , 30 or other close contacts, 16 – 19 , 22 , 24 , 25 , 32 – 34 , 36 , 39 , 42 , 44 , 46 48 , 52 including individuals outside the household. Of the latter studies of close contacts, many reported SARs among household contacts, 17 , 18 , 22 , 24 , 25 , 32 – 34 , 36 , 39 , 42 , 44 , 46 48 , 52 or all family members. 16 , 19 – 21 , 23 , 27 , 30 We did not include studies of close contacts that did not report SARs for household or family members.…”
Section: Review Of Transmissibility Of Sars-cov-2 In Households and Fmentioning
confidence: 99%
See 3 more Smart Citations